The effects of attentional bias modification on emotion regulation - Van Bockstaele, B.; Notebaert, L.; MacLeod, C.; Salemink, E.; Clarke, Patrick; Verschuere, B.; Bögels, S.; Wiers, R. (Elsevier BV; North Holland, 2019)
© 2018 Elsevier Ltd Background and objectives: In two experiments, we investigated the effects of Attentional Bias Modification (ABM) on emotion regulation, i.e. the manner in which people influence emotional experiences. We hypothesized that decreases in attentional bias to threat would impair upregulation and improve downregulation of negative emotions, while increases in attentional bias to threat would improve upregulation and impair downregulation of negative emotions. Methods: Using the emotion-in-motion paradigm (Experiment 1, N = 60) and the visual search task (Experiment 2, N = 58), we trained participants to attend to either threatening or positive stimuli and we assessed emotion intensity while observing, upregulating, and downregulating emotions in response to grids of mixed emotional pictures. Results: In Experiment 1, the attend positive group reported more positive emotions while merely watching grids of training pictures and the attend threat group showed impaired upregulation of negative affect. In Experiment 2, the attend threat group reported intensified negative emotions for all three instructions, while the attend positive group remained largely stable over time. Limitations: We cannot unequivocally attribute these changes in emotion regulation to changes in attentional bias, as neither of the experiments yielded significant changes in attentional bias to threat. Conclusions: By showing that attentional bias modification procedures affect the manner in which people deal with emotions, we add empirical weight to the conceptual overlap between attentional bias modification and emotion regulation.